The runaway king [compact disc, unabridged] - Nielsen, Jennifer A. (Nielsen, Jennifer A. Ascendance series, 2013)
Young King Jaron has taken the throne of Carthya, but, after enemies attempt to assassinate him and a neighboring kingdom threatens invasion, he finds that he has no friends in the palace, not even his bride-to-be, princess Amarinda-- and his regents think it would be better for Carthya if he just disappeared again.